Building on a YMCA's health and physical activity promotion capacities: A case study of a researcher-organization partnership to optimize adolescent programming_. (August 2016) - Bush, Paula Louise; García Bengoechea, Enrique
Highlights: We used a participatory research approach to evaluate a YMCA's teen program. Our collaboration helped the YMCA shift from acting on intuition to acting on insight. The YMCA maintained the evaluation process and plans to expand it. We propose a new conceptualisation of the New South Wales capacity building framework. We suggest how partnership synergy theory and capacity building may operate together. Abstract: School-based physical activity programs are only effective for increasing adolescents' school-based physical activity. To increase out-of-school-time physical activity, complementary community programs are warranted. Partnerships between universities and community organizations may help build the capacity of these organizations to provide sustainable programs. To understand capacity building processes and outcomes, we partnered with a YMCA to build on their adolescent physical activity promotion capacity. Together, we designed and implemented means to evaluate the YMCA teen program to inform program planning. For this qualitative case study, emails and interviews and meetings transcripts were collected over 2.5 years and analyzed using inductive and deductive thematic analysis. Findings illustrate that the YMCA's workforce and organizational development capacities (e.g., evaluation and health promotion capacity and competence) were increased through our partnership, resource allocation, and leadership. We responded to YMCA partners' perceived needs, yet guided them beyond those needs, successfully combining our complementary objectives, knowledge, and skills to generate an integrated program vision, rationale, and evaluation results. This provided YMCA partners with validation, reminders, and awareness. In turn, this contributed to programming and evaluation practice changes. In light of extant capacity building literature, we discuss how our partnership increased the YMCA's capacity to promote healthy adolescent programs.